Calidad de atención al cliente en la Cooperativa JEP del cantón Puebloviejo - Mosquera Zambrano, Helen Carolina (2021)
The importance of customer service is increasingly an important factor for the management of public or private institutions, because customers or users are currently looking for quality products and services accompanied by timely, efficient and effective attention, which represents an added value in the development of internal activities in organizations. The study on the quality of care in the Cooperativa de Ahorro y Crédito JEP aims to analyze business activities related to the customer service process and how they influence the perception of users in access to financial products and services offered by the institution. The methodology of the project is made up of the types of descriptive and field research, because all the information obtained from the observation subjects is administered for the identification of the main problematic facts, in addition the inductive and deductive methods were applied, supported by the use of the survey as a technique, which has a questionnaire addressed to users of financial products that allowed obtaining as main conclusions a limited physical space in the mediations of the Cooperativa de Ahorro y Creditos JEP, agency of the Puebloviejo canton, absenteeism, complacent advice on the institution's services, weak empowerment of the processes by human talent and inadequate response to requests incomplaints and claims; Main weaknesses that affect the institutional image with respect to the care process.